1990
DOI: 10.1055/s-2008-1046191
|View full text |Cite
|
Sign up to set email alerts
|

Changements de la concentration du K+induits par un flash dans le vitré prérétinien du porc miniature anesthésié

Abstract: When measured with double-barreled ion-selected microelectrodes, delta K+0 is found to be heterogeneously distributed over the retinal surface. A transient fall (less than or equal to 200 microM) in delta K+0 near an arteriole wall and a transient increase (less than or equal to 500 microM) in zones free of arterioles were observed during light stimulation. In view of these findings the authors assume that the former is due to K+ uptake and transport by perivascular astrocytes, and that the latter is due to K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several approaches have been tried to investigate blood flow change in the retina during neuronal stimulation in humans [10,8,12,13,14,17,25,26,27,28,30,31,32,33,39,40,42,37,44,45,52]. In one study the blue-field entoptic technique was used and an increase in retinal white blood cell flux in response to flicker stimulation was reported in healthy volunteers [44].…”
Section: Comparison To Existing Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches have been tried to investigate blood flow change in the retina during neuronal stimulation in humans [10,8,12,13,14,17,25,26,27,28,30,31,32,33,39,40,42,37,44,45,52]. In one study the blue-field entoptic technique was used and an increase in retinal white blood cell flux in response to flicker stimulation was reported in healthy volunteers [44].…”
Section: Comparison To Existing Workmentioning
confidence: 99%
“…Recent investigations with techniques assessing ocular blood flow have shown that such a mechanism operates at the optic nerve head and retina in cats [5,18,38,36,47,51], rabbits [50], mini-pigs [31], primates [2,3,15] and humans [8,9,10,11,12,13,14,17,25,26,27,28,30,32,31,33,39,40,41,42,44,45,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cat and rat, individual astrocytes can be simultaneously engaged in contacts with both vessels and axonal bundles. In the rat retina, this feature is not readily visible by conventional fluorescence microscopy and the usefulness of confocal microscopy appears evident, since optic nerve humour and the vasculature provided by intercalating astrocytes would accommodate a recent electrophysiological observation in the miniature pig, where, after a light flash, the amplitude of change in extracellular potassium concentration in the preretinal vitreous was found to depend on the distance between the site of measurement and the neighbouring vessel (Poitry-Yamate et al, 1990). This observation has been tentatively explained by an uptake of potassium from the vitreous body by perivascular astrocytes and its release into the vessel.…”
Section: Discussionmentioning
confidence: 96%